Ezekiel's oracles against the nations in light of a royal ideology of warfare - Crouch, C.L. (Society of Biblical Literature, 2011)
Over the last few decades a steady stream of scholarship has argued for a mythological background to the oracles against the nations (OANs) in the book of Ezekiel.1 Very few studies, however, have attempted to make overarching sense of Ezekiel’s use of mythological motifs, either in the oracles or as part of the theological and literary project of the book. This essay will argue that Ezekiel’s use of mythological motifs of a cosmological type, both in the cycle of OANs and as part of the book as a whole, is derived from the royal military ideology that was current in Jerusalem prior to the exile, and that the oracles constitute a direct attempt to incorporate the experience of exile into this ideology. Ultimately, however, Ezekiel’s initial efforts to this end were perceived to have failed, and alternative ideological explanations of warfare were introduced, either by Ezekiel himself or by an editor. I will conclude by addressing the accrual of this additional material.